2020
DOI: 10.2147/hiv.s242784
|View full text |Cite
|
Sign up to set email alerts
|

<p>An Analytical Comparison of Knowledge, Attitudes, and Practices Regarding HIV/AIDS Among Medical and Non-Medical Students in Iran</p>

Abstract: Background and Objectives: Young people are the main group at risk of HIV/AIDS due to factors such as curiosity, peer pressure, lack of knowledge and skills, unsafe sexual behaviors, and drug abuse. The present study was conducted to compare the knowledge, attitudes, and practices regarding HIV/AIDS among medical and non-medical students in Iran. Methods: This cross-sectional descriptive-analytical study was conducted on a population consisting of the students of Shahid Beheshti University (SBU) and Shahid Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Similar to the findings from Jimma University [12], Mizan-Tepi University [13], Bahir Dar University [14], and Ethiopian Civil Service College students [15], the present study also ob- served some misconceptions among the participants on different aspects of the disease. The overall knowledge of the students on the modes of transmission and prevention was good, and the knowledge was higher among CHS students (89.3%) comparing with FBE (66.2%), which is in line with a study done at Madda Walabu University, Southeast Ethiopia [16] and Iran [17]. A possible justification for higher knowledge of health science students is that they get such kind of information in some courses as part of their curriculum.…”
Section: Knowledge On Hiv/aidssupporting
confidence: 82%
“…Similar to the findings from Jimma University [12], Mizan-Tepi University [13], Bahir Dar University [14], and Ethiopian Civil Service College students [15], the present study also ob- served some misconceptions among the participants on different aspects of the disease. The overall knowledge of the students on the modes of transmission and prevention was good, and the knowledge was higher among CHS students (89.3%) comparing with FBE (66.2%), which is in line with a study done at Madda Walabu University, Southeast Ethiopia [16] and Iran [17]. A possible justification for higher knowledge of health science students is that they get such kind of information in some courses as part of their curriculum.…”
Section: Knowledge On Hiv/aidssupporting
confidence: 82%
“…Health education enhances AIDS-related attitudes, knowledge, and behavior [10,11], such as lectures and group discussions. Peer education effectively enhances the students' knowledge and changes their attitudes [12,13]. In our study, 3.4% of students had sexual behavior.…”
Section: Discussionmentioning
confidence: 59%
“…In the present study, there was a significant difference in terms of practice between married and single people, and married employees had a better practice. As other studies have shown, married medical students perform better [28,35,36]. This may be due to their direct involvement in sexual activity, and thus, they better understand the consequences of not following health tips during sex, which can lead to their better practice comparing to single people.…”
Section: Discussionmentioning
confidence: 79%
“…As studies show, medical students have a low negative attitude towards sexually transmitted diseases, such as AIDS, and their education increases their experience and improves their attitude [32][33][34][35] that it can affect the practice. In our study, total practice was optimal and it seems that midwives had a better practice.…”
Section: Discussionmentioning
confidence: 99%